2018
DOI: 10.1111/pbr.12624
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to the peach root‐knot nematode (Meloidogyne floridensis) in interspecific crosses between peach (Prunus persica) and its wild relative (Prunus kansuensis)

Abstract: The peach root‐knot nematode, Meloidogyne floridensis (MF), infects majority of available nematode‐resistant peach rootstocks which are mostly derived from peach (Prunus persica) and Chinese wild peach (P. davidiana). Interspecific hybridization of peach with its wild relative, Kansu peach (P. kansuensis), offers potential for broadening the resistance spectrum in standard peach rootstocks. We investigated the inheritance of resistance to MF in segregating populations of peach (‘Okinawa’ or ‘Flordaguard’) × P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…A major gene conferring genetic resistance to M. incognita was identified on LG2 (Cao et al 2011) and cosegregates with a nucleotide-binding site-leucine rich repeat (NBS-LLR) gene (Cao et al 2014). In the same linkage group, a recent study has reported a major locus with dominant/recessive allele that confirms P. kansuensis as a source of resistance to this newly discovered threat in peach, M. floridensis, (Maquilan et al 2018a), this Mf gene, has been mapped in linkage group 2 (Maquilan et al 2018b). Whether the Mf, RMia and PkMi are distinct genes that are tightly linked in a single locus or are part of a single multi-allelic resistance locus is an open question that still needs further studies to elucidate (Saucet et al 2016).…”
Section: Pests and Diseases Tolerance/resistancementioning
confidence: 84%
“…A major gene conferring genetic resistance to M. incognita was identified on LG2 (Cao et al 2011) and cosegregates with a nucleotide-binding site-leucine rich repeat (NBS-LLR) gene (Cao et al 2014). In the same linkage group, a recent study has reported a major locus with dominant/recessive allele that confirms P. kansuensis as a source of resistance to this newly discovered threat in peach, M. floridensis, (Maquilan et al 2018a), this Mf gene, has been mapped in linkage group 2 (Maquilan et al 2018b). Whether the Mf, RMia and PkMi are distinct genes that are tightly linked in a single locus or are part of a single multi-allelic resistance locus is an open question that still needs further studies to elucidate (Saucet et al 2016).…”
Section: Pests and Diseases Tolerance/resistancementioning
confidence: 84%
“…Additionally, a Chinese wild peach (P. kansuensis) has been shown to carry an R gene to M. incognita named PkMi [54,55], which is also located on LG2, but its relationship with RMia needs to be clarified. An accession of P. kansuensis has also been proposed by other authors as carrying a single-locus dominant (Mf )/recessive (mf ) model for the inheritance of resistance to M. floridensis [56], as the cognate Mf locus is also located on LG2 [57]. It will be important to determine the spectrum of this resistance towards other RKN species and to shed light on the relationship between the RMia, PkMi and Mf genes from peach resistance sources.…”
Section: Genetics and Mapping Of Rkn Resistancementioning
confidence: 99%
“…Flordaguard rootstock found growing in the UF stone fruit orchard. This isolate was used subsequently for genetic studies of resistance in peach rootstocks (Maquilan et al, 2018a(Maquilan et al, , 2018b, as well as comparative genomics of RKN (Szitenberg et al, 2017). The MfGnv14 inoculum used for the current study was collected after two cycles (6 months) of propagation on tomato, whereas the other M. floridensis isolates were maintained over 10 years on greenhouse grown tomato.…”
Section: Nematode Isolatesmentioning
confidence: 99%
“…in Flordaguard (Maquilan et al, 2018a), Okinawa (Sharpe et al, 1969), and Flordaglo (Chaparro, per. comm.).…”
Section: Journal Of Nematologymentioning
confidence: 99%
See 1 more Smart Citation